PENGARUH PENERAPAN STRATEGI PEMBELAJARAN GALLERY WALK MATA PELAJARAN IPS TERHADAP KEAKTIFAN BELAJAR YANG MEMILIKI MOTIVASI BELAJAR BERBEDA DI MI AL-FITHRAH SURABAYA - Putri, Febby Dwi Kusuma (Journal Of Islamic Elementary School (JIES), 2018)
This research aims to find out: (1) There are differences in student learning activeness which are treated with Gallery Walk learning strategies with conventional learning strategies, (2) There are differences in learning activity of students who have high learning motivation with those who have low learning motivation, (3) The interaction between Gallery Walk learning strategies, conventional strategies and student learning motivation towards student learning activeness. This study uses a quantitative approach with the quasy experimental method. The study design used a non equivalent control group design. The data of this study were obtained by interview, observation and questionnaire techniques. Data analysis using Two Way ANOVA test on all hypothesis testing. The results of the study show: (1) There is an influence of the Gallery Walk learning strategy on student learning activeness. The average score of learning activeness of students who were treated using Gallery Walk learning strategy was 84.3 better than the average score of learning activeness of students who were treated with conventional strategies, namely 62. (2) There were influences of students who had high learning motivation towards activity learn. The average score of learning activeness of students who have high motivation is 54.7 better than the average score of low learning motivation which is 45.3. (3) There is an interaction effect between gallery walk learning strategies, conventional strategies and student learning motivation towards student learning activeness.